The LGBT community in Israel: access to the surrogacy procedure and legal right for equality, family life and parenthood - Ilany, Yael; Ilany, Netta (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2021)
In Israel’s legal system, equality is a fundamental principle. LGBT people in Israel suffer from discrimination due to their sexual orientation and their right to equality, parenting, and family life is impaired. Regarding the surrogacy procedure, the Supreme Court has unequivocally stated that the relevant laws discriminate against LGBT people and their fundamental rights when compared to heterosexual people. The main problem is that the statutes block the access to the surrogacy procedure of single men and male couples, harming their right to equality, right to a family life and parenting. The article suggests adopting the minority ruling of Justice Uzi Vogelman in HCJ 781/15 and declaring the nullity of the sections in the laws that discriminate against single men and male couples. This remedy is a lawful and operative solution for the inequality rooted in the surrogacy arrangements towards homosexuals that want to establish a family and become parents. The expectation from the legislature to amend the law is unrealistic, due to the political construction of the Israeli Knesset (parliament). An innovative approach for the amendment of the inequality towards LGBT people should be the nullity of the discriminating sections of the law.